Acceptability of male circumcision for HIV prevention among men who have sex with men in China: a short report. Issue 3 (4th March 2022) - Yuan, Tanwei; Gao, Yanxiao; Wang, Zhenyu; Huang, Ruonan; Wang, Junfeng; Li, Peiyang; Meng, Xiaojun; Zhang, Kechun; Wang, Guanghui; Zhou, Yepeng; Luo, Danyang; Cai, Yong; et al.
ABSTRACT: Recent evidence shows that circumcision is associated with lower HIV prevalence among MSM. We assessed the acceptability of circumcision for preventing HIV and that of Shang Ring circumcision (SRC) among men who have sex with men (MSM) in China. 538 adult MSM were recruited from six cities in China between January and March 2019. Participants were surveyed by an online, self-administered questionnaire. The acceptability of circumcision was assessed before and after the potential protective effect of circumcision against HIV was informed, and subsequently men's willingness to undergo SRC was assessed. The level of circumcision was 16.4%. Of 450 uncircumcised MSM, their willingness to be circumcised in the following six months increased significantly from 32.2% to 55.6% after the information session. Three quarters of men who were willing to undergo circumcision accepted SRC. MSM who perceived that circumcision could maintain genital hygiene were more likely to accept circumcision after the information session, whereas those who regarded circumcision as an embarrassing surgery were disinclined to be circumcised. The low circumcision rate, along with its high acceptability in Chinese MSM, suggests a great potential benefit of circumcision intervention if proved effective. SRC might be a popular circumcision procedure in this population.